EVALUASI PROGRAM BROADBAND LEARNING CENTER DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA LUBUKLINGGAU - Nur Asih Kurnia Sari; Heni Nopianti; Lailatus Sa'diyah (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2022)
The purpose of the study was to determine the implementation of programs related to the evaluation of the Program  Broadband Learning Center at the Lubuklinggau City Library and Archives Service. The research method is descriptive quantitative. The research sample totaled 93 (ninety three) respondents from participants who attended training in 2017, 2018, 2019, and the samples were taken randomly. The results of the component research input obtained a result of 4.09 (four point nine blanks) included in the Good criteria. The component Activities and Processes obtained a result of 3.84 (three point eighty four) included in the Good criteria, but there were 2 (two) statements in this component that obtained an average score with poor criteria.The component Output obtained a result of 4.10 (four point ten) which is included in the Good criteria. The results of the recapitulation of the components Input, Activities and processes, as well as the Output of 4.01 (four point blank one) are included in the Good criteria with the predicate successful.